Looking through the bamboo curtain: an analysis of the changing role of forest and farm income in rural livelihoods in China - Ruíz Pérez, M.; Belcher, B.; Fu Maoyi; Yang Xiaosheng (2004)
Forestry and poverty analyses in China show an ambiguous relationship. While the co-occurrence of forest rich areas and poor counties has been noted by some authors, others have stressed the role played by forestry in these areas where it is frequently one of the few options available. This study indicates that the expansion of off-farm income is the fundamental development process taking place in many areas of rural China. Forestry can offer good income generating options to farmers, but as the local economy develops forestry tends to be displaced by more attractive alternatives. There are niche specialisation opportunities even for rich farmers, normally linked to a certain degree of vertical integration, enhanced by specific features of some forestry uses like bamboo.